Pengembangan Literasi Hukum sebagai Bagian dari Civic Literacy Peserta Didik di Era Digital - Khairul Anwar; Indriani (Innovations in Multidisciplinary Education Journal, 2026)
Digital transformation has given rise to various legal issues related to privacy, personal data protection, cyberbullying, freedom of expression, and the use of digital content. Consequently, legal literacy needs to be developed as an integral component of students’ civic literacy. This study aims to analyze the current state and needs of legal literacy, examine its relationship with civic literacy, and develop legal literacy learning materials that are aligned with the characteristics of students in the digital era. A mixed-methods approach was employed using an Educational Design Research design consisting of three stages: analysis and exploration, design and construction, and evaluation and reflection. The study was conducted at Karya Bakti Senior High School in Bukittinggi and involved students, Pancasila Education teachers, and expert validators. Data were collected through questionnaires, interviews, observations, expert validation, and tests. The data were analyzed using descriptive statistics, correlation analysis, paired-samples t-tests, and thematic analysis. The findings indicate that students’ initial legal literacy was at a moderate level, with a mean score of 60.5. Legal literacy was found to have a positive relationship with civic literacy (r = 0.67; p < 0.001), with the strongest association identified in the dimension of responsible response (r = 0.71). The developed learning materials achieved a feasibility score of 90.8% and were categorized as highly feasible. Following implementation, the mean legal literacy score increased from 60.5 to 82.6, while the civic literacy score increased from 68.1 to 83.4, with statistically significant differences (p < 0.001). These findings indicate that the development of digital case-based legal literacy learning has the potential to strengthen students’ civic literacy by enhancing their ability to understand rights and responsibilities, analyze legal issues, assess the consequences of actions, and determine responsible civic responses.